POSTMODERNISME VERSUS MODERNISME - Agustinus Ryadi (Litbang STFT Widya Sasana Malang, 2004)
Postmodernism has been a buzzword in contemporary society for the last decade. Postmodernism becomes a new trend shaking in philosophy world. It is shaking because postmodern thoughts attack modern thought. In postmodernism side, represented by Jean-François Lyotard, totality thought which is the main character of modernism is only a failure. When the totality is nothing, so it means the death of metanarrative. This is a postmodern critique that delivers modernism to defend itself. Jürgen Habermas from the modernism assumed that totality is really important in defending the integrity of society and culture. This article shows the argumentations quarrel between Lyotard and Habermas.